KUALITAS IMPLEMENTASI PELAYANAN RAMAH ANAK DI PUSKESMAS-PUSKESMAS KABUPATEN BANTUL - Safira Zata Yumni; Fauzian Nur Azizah; Maska Septafiya Angesti; Andreas Deddy Eko Nugroho (Jurnal Riset Daerah, 2023)
Pusat Kesehatan Masyarakat (Puskesmas) is a health facility unit that carries out basic-level public and individual health efforts that are promotive, preventive, curative, and rehabilitative in nature, including health services for mothers and children. Therefore, a puskesmas needs to develop child-friendly services. The aim of this research is to analyze the implementation and quality of child-friendly services at puskesmas in Bantul Regency. The method used in this research is descriptive-quantitative. Data was collected using questionnaire forms and then edited, scored, weighted, and classified based on the measurement by Kementrian Pemberdayaan Perempuan dan Perlindungan Anak. The research results showed that there are nine puskesmas categorized as Utama level, twelve belonging to Nindya level, and five classified Madya level. However, there is only one puskesmas in Bantul Regency which is eligible as Puskesmas Ramah Anak, namely Puskesmas Kasihan I. The quality of PRAP implementation in Bantul Regency is good because more than 78% of Puskesmas in Bantul Regency have implemented mother and children health services to support organizing KLA through health programs and innovation activities. Measurement of the quality of implementation of child-friendly services at community health centers is conducted based on the fulfillment of each child-friendly service variable contained in the institutional cluster as well as the basic health and welfare cluster.